Shell-and-tube or packed bed thermal energy storage systems integrated with a concentrated solar power: A techno-economic comparison of sensible and latent heat systems. (15th March 2019) - Mostafavi Tehrani, S. Saeed; Shoraka, Yashar; Nithyanandam, Karthik; Taylor, Robert A.
Highlights: Alternative PCM and sensible TES designs were compared in an integrated CSP system. The role of CSP plant off-design operation on alternative TES viability is highlighted. The optimal dual-media TES design has ∼150 m 2  m −3 specific surface area. A concrete, packed bed design provides the best techno-economic performance. The wall thickness of the PCM container represents a barrier against their feasibility. Abstract: A detailed techno-economic comparison—using annual, transient integrated system modelling—was conducted for sensible and latent heat thermal energy storage (TES) systems. As the most viable near-term competitors, thermocline/packed-bed and shell-and-tube configurations were compared to the conventional two-tank molten salt system. Concrete and a range of phase change materials (PCMs) were considered as the storage mediums in this study. All analyses were conducted for 15 h of storage capacity for the 19.9 MWe Gemasolar concentrated solar power (CSP) plant as a real-world case study. It was found that when the CSP plant is constrained to the operational within the tight bounds of the standard two-tank system, the dual-media thermocline (DMT) system with concrete or encapsulated PCM shows the best performance. Imposing rigid operational boundaries significantly disadvantages shell-and-tube (ST) systems (e.g. resulting in up to ∼50% less annual electricity production than a CSP plant with two-tank system). However, the results of this study reveal that extending the TES charge and discharge cut-off temperatures closer to the plant's maximum and minimum operating range (i.e. 800 K and 650 K) can maximize the potential of dual-media TES alternatives. Under these loose operational conditions, the CSP plant will be required to occasionally operate at conditions which are far from its nominal design point (i.e. up to 75% variation). This flexibility allows all the TES alternatives considered in this study to achieve similar CSP annual electricity output as the two-tank system. In this case (e.g. all TES systems achieve the same annual output), the TES alternatives can be compared based on their specific costs rather than their levelized cost of electricity. Compared to the specific cost of two-tank molten salt systems, ∼24.5 US$ kWhth −1, a 62% reduction of specific storage cost was found to be achievable with concrete storage a dual-media thermocline (DMT) system, representing the best techno-economic option. This was followed by 49% cost reduction for a pipeless shell-and-tube (ST) system incorporating concrete or a PCM with 1 mm pipe thickness. Without minimizing the capsule thickness to 0.1 mm, the packed bed system with PCM would never have economic justification. Overall, this study reveals that if CSP systems can be designed to have more flexibility in their operational temperature range, a significant cost savings is available in moving to alternative TES systems.